Major life stress, coping styles, and social support in relation to psychological distress in patients with systemic lupus erythematosus - Kozora, E; Ellison, M C; Waxmonsky, J A; Wamboldt, F S; Patterson, T L (Lupus, 2005)
The objective of this study was to examine psychological processes in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) patients in relation to measures of life stress, coping styles, social support and cognitive ability. Fifty-two SLE patients without overt neuropsychiatric symptoms, 29 RA patients and 27 healthy controls completed measures of depression, mood, disease activity, perceived health, stressful life events, coping, and social support. Variables entered into the multiple regression analysis following principal component analysis were: group, major difficult event, major life threatening event, disengaging coping, emotional coping, social support, and cognitive impairment. Depressive symptoms were associated with SLE group status (P, 0.001), major life-threatening events (P, 0.01), disengage coping (P, 0.001) and emotional coping (P, 0.05). SLE group status (P, 0.05), disengage coping (P, 0.05) and emotional coping (P, 0.05) were associated with current distressed mood. SLE patients without overt, major neuropsychiatric symptoms had greater psychological distress compared to RA and control subjects. Increased depressive symptoms and distressed mood state in SLE patients were related to use of disengaging and emotional coping styles. These findings are limited to SLE patients with no overt neuropsychiatric illness and low disease activity, suggesting the need for future studies with a greater variety of SLE patients. Interventions aimed at improving active coping and minimizing emotional response to stress may lower psychological distress in SLE patients with mild disease.